Comparison of cerebral blood flow and structural penumbras in relation to white matter hyperintensities: A multi-modal magnetic resonance imaging study. Issue 9 (September 2016) - Promjunyakul, Nutta-on; Lahna, David L; Kaye, Jeffrey A; Dodge, Hiroko H; Erten-Lyons, Deniz; Rooney, William D; Silbert, Lisa C
Normal-appearing white matter (NAWM) surrounding WMHs is associated with decreased structural integrity and perfusion, increased risk of WMH growth, and is referred to as the WMH penumbra. Studies comparing structural and cerebral blood flow (CBF) penumbras within the same individuals are lacking, however, and would facilitate our understanding of mechanisms resulting in WM damage. This study aimed to compare both CBF and structural WMH penumbras in non-demented aging. Eighty-two elderly volunteers underwent 3T-MRI including fluid attenuated inversion recovery (FLAIR), pulsed arterial spin labeling and diffusion tensor imaging (DTI). A NAWM layer mask was generated for periventricular and deep WMHs. Mean CBF, DTI-fractional anisotropy (DTI-FA), DTI-mean diffusivity (DTI-MD) and FLAIR intensity for WMHs and its corresponding NAWM layer masks were computed and compared against its mean within total brain NAWM using mixed effects models. For both periventricular and deep WMHs, DTI-FA, DTI-MD and FLAIR intensity changes extended 2-9 mm surrounding WMHs (p ≤ 0.05), while CBF changes extended 13-14 mm (p ≤ 0.05). The CBF penumbra is more extensive than structural penumbras in relation to WMHs and includes WM tissue both with and without microstructural changes. Findings implicate CBF as a potential target for the prevention of both micro and macro structural WM damage.